Male Earnings Inequality, Women’s Earnings, and Family Income Inequality in Australia, 1982–2007 - Austen, Siobhan; Redmond, G. (M.E. Sharpe, Publisher, 2013)
In the quarter century after 1982, male earnings inequality increased substantially in most industrialized countries, as did women’s participation in paid work. Both trends impacted family income inequality. However, this paper’s analysis of Australian data shows that the impact of women’s earnings on family income inequality changed over the study period of 1982 to 1995–1996. During the same time frame, the growth in women’s earnings was concentrated in households with high male earnings, pushing family income inequality higher. However, after 1995–1996, the growth in women’s earnings had a moderating influence on family income inequality as it was concentrated in households with lower male earnings. These findings contribute new evidence on the importance of trends in family formation and the correlation of husbands’ and wives’ earnings to the evolution of family income inequality. The evidence is also suggestive of a dynamic relationship between rising family income inequality and women’s participation in paid work that echoes Thorstein Veblen’s ([1899] 2008) ideas regarding the importance of relative income and emulation.